Marriage in Past, Present and Future Tense - Carsten, Janet; Chiu, Hsiao-Chiao; Magee, Siobhan; Papadaki, Eirini; Reece, Koreen M. (UCL Press, 2021)
Marriage globally is undergoing profound change, provoking widespread public comment and concern. Through the close ethnographic examination of case studies drawn from Africa, Asia, Europe and North America, Marriage in Past, Present and Future Tense places new and changing forms of marriage in comparative perspective as a transforming and also transformative social institution. In conditions of widespread socio-political inequality and instability, how are the personal, the familial and the political co-produced? How do marriages encapsulate the ways in which memories of past lives, present experience and imaginaries of the future are articulated? Exploring the ways that marriage draws together and distinguishes history and biography, ritual and law, economy and politics in intimate family life, this volume examines how familial and personal relations, and the ethical judgements they enfold, inform and configure social transformation. Contexts that have been partly shaped through civil wars, cold war and colonialism - as well as other forms of violent socio-political rupture - offer especially apt opportunities for tracing the interplay between marriage and politics. But rather than taking intimate family life and gendered practice as simply responsive to wider socio-political forces, this work explores how marriage may also create social change. Contributors consider the ways in which marital practice traverses the domains of politics, economics and religion, while marking a key site where the work of linking and distinguishing those domains is undertaken.